Economic evaluation of facility‐based HIV self‐testing among adult outpatients in Malawi. Issue 9 (9th September 2020) - Nichols, Brooke E; Offorjebe, O Agatha; Cele, Refiloe; Shaba, Frackson; Balakasi, Kelvin; Chivwara, Mackenzie; Hoffman, Risa M; Long, Lawrence C; Rosen, Sydney; Dovel, Kathryn
Abstract: Introduction: HIV self‐testing (HIVST) in outpatient departments (OPD) is a promising strategy for HIV testing in Malawi, given high OPD patient volumes and substantial wait times. To evaluate the relative cost and expected impact of facility‐based HIVST (FB‐HIVST) at OPDs in Malawi for increasing HIV status awareness, we conducted an economic evaluation of an HIVST cluster‐randomized controlled trial. Methods: A cluster‐randomized trial was conducted at 15 sites in Malawi from September 2017 to February 2018 with three arms: 1) Standard provider‐initiated‐testing‐and‐counselling (PITC); 2) Optimized PITC (additional provider training and job‐aids) and 3) FB‐HIVST (HIVST demonstration, distribution and kit use in OPD, private kit interpretation and optional HIV counselling). The total production cost per newly identified positive and per person newly initiated on ART were calculated by study arm. These were calculated as the total cost of testing everyone divided by the number of newly identified positives; and the total cost of testing everyone divided by the number of those initiated on ART. Cost‐outcomes were calculated under three cost scenarios: (1) full study costs, (2) routine implementation costs and (3) routine implementation + reduced cost for HIVST kits. Results: The average cost per person newly diagnosed in the full study cost scenario was $101, $156 and $189, and cost per person initiated on ART was $121, $156 and $279 for Standard PITC, Optimized PITC and FB‐HIVST respectively. In the routine implementation cost scenario, the average cost per person newly diagnosed was reduced to $83, and $93, and cost per person initiated on ART to $83, and $137 for Optimized PITC and FB‐HIVST respectively. In the negotiated HIVST cost scenario, the average cost per person newly diagnosed was reduced to $55 and cost per person newly initiated on ART reduced to $81 in the FB‐HIVST arm. Conclusions: While the cost per new ART initiation through FB‐HIVST was higher than Standard PITC, FB‐HIVST could become cost‐saving compared to PITC if the cost of kits is reduced or if treatment linkage rate were increased in the FB‐HIVST arm. For high volume OPDs, HIVST may increase facility capacity and increase the number of newly diagnosed positives.